Stereogame – Desenvolvimento, implementação e avaliação de um jogo didático-computacional para o ensino de estereoquímica - Moreira, João Victor Xerez (2016)
Games and software are excellent methods of active learning and have been increasingly used in different areas of education in addition to traditional methods, to facilitate the teaching-learning process. In this work, using the Flash Platform, a didactic computer game was developed. Stereogame is a card /board game, free of charge and in two languages (Portuguese and English), which addresses the issue of stereochemistry. Access to the game was made available on the homepage of the Federal University of Ceará’s Chemistry Course (http://www.quimica.ufc.br/stereogame). The game was rated by students and teachers. The evaluation results characterize the game as a good educational tool, allowing students to review the content covered in stereochemistry in a playful way, facilitating their learning. The versatility of the game format has also been proven through its easy adaptation to the theme of Sciences, in a partnership with an elementary and middle school – Espaço Vida. In this case, only changing the set of questions and some template details, Stereogame was transformed into a general Science game.